2021
DOI: 10.18421/tem104-45
|View full text |Cite
|
Sign up to set email alerts
|

STEAM Education in the View of the Bulgarian Teacher

Abstract: The reality we live in is constantly changing, modern technologies comprise all spheres of life, changing it irreversibly. These transformations require completely different knowledge, skills, and especially competencies with the modern human. To meet these needs adequately, the educational system is also changing - new approaches, methods, and technologies of teaching are being introduced. The purpose of the study, which found a place in this report, is to examine the teacher's position and opinion on the ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Apart from their contributions to society, GC also benefits the students personally and academically as studies have shown students are more culturally sensitive than their teachers (Carter, 2020). is credited to Engineering and Technology teacher Georgette Yakman, who in 2006 founded the STEAM educational framework (Topalska, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their contributions to society, GC also benefits the students personally and academically as studies have shown students are more culturally sensitive than their teachers (Carter, 2020). is credited to Engineering and Technology teacher Georgette Yakman, who in 2006 founded the STEAM educational framework (Topalska, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…STEM-based project-based learning is a type of project-based learning that incorporates STEM subjects, notably science, technology, engineering, and mathematics. STEM education benefits students by fostering their critical thinking and competencies necessary for success in the profession and in resolving everyday challenges (Topalska, 2021). STEM education teaches pupils to be creative, analytical, and critical thinkers (Nurtanto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some schools incorporate STEAM in their teaching approaches (Hawari & Noor, 2020). STEAM stands for Science, Technology, Engineering, Arts, and Mathematics (Sakon & Petsangsri, 2021;Dolgopolovas & Dagienė, 2021;Topalska, 2021;Kwan & Wong, 2021;Xue, 2022). Essentially, it is an educational approach aimed at fostering early interest and love for both art and science among children (Rodríguez-Nieto & Alsina, 2022).…”
Section: Introductionmentioning
confidence: 99%